Pelatihan Dan Pendampingan Akuntabilitas Dalam Pengelolaan Dana Seni Dan Kirab Budaya Pada Desa Cupak Jombang - Irda Agustin Kustiwi; Binti Yuliatin; Dhea Rizky Istiqomah; Nur Wahyu Satriwibowo; Adelia Febriana; Gusti Chania Raafi Iradati (Universitas Kristen Indonesia Toraja, 2023)
Accountability in village governance is crucial to ensure responsible government oversight of village financial management and prevent misappropriation. Cupak Village, renowned as a religious tourism destination in Gunung Pucangan, possesses potential in the craft of weaving mats using pandan leaves. However, the village community lacks the capacity to fully utilize this potential as an additional source of income. To address various issues faced by the community, particularly in establishing accountability in event fund management for a cultural parade called